2005
DOI: 10.1029/2005gl023023
|View full text |Cite
|
Sign up to set email alerts
|

Features in wavelength dependence of aerosol absorption observed over central India

Abstract: Measurements on spectral dependence of aerosol light absorption and BC mass concentrations were made at various locations between Ahmedabad (23.03°N, 72.50°E) and Hyderabad (17.47°N, 78.45°E) during February 2004. Average concentration of BC was close to 2 μg/m3 which is about 2 to 5% of the total aerosol mass loading measured at the surface. Absorption Angstrom coefficient estimated using a relation of the form βabs(λ) = K.λ−α is found to vary between 1.2 to 2.0 at different locations. Our result shows an exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…The M BC reported by us was measured at a wavelength of 880 nm. The reason for this choice was that the BC is the principal absorber at this wavelength (Ganguly et al, 2005). The sample flow rate to the aethalometer was 3 L/min at a scan time of 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The M BC reported by us was measured at a wavelength of 880 nm. The reason for this choice was that the BC is the principal absorber at this wavelength (Ganguly et al, 2005). The sample flow rate to the aethalometer was 3 L/min at a scan time of 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The spectral dependence of absorption (i.e., AAE) depends upon particle size and the imaginary refractive index, and excellent overviews of the relationship between AAE and aerosol microphysics are provided by Moosmüller et al (2009Moosmüller et al ( , 2011. Generally, AAE is obtained from photoacoustic measurements (Lewis et al, 2008;Chow et al, 2009;Gyawali et al, 2009;Flowers et al, 2010;Lack et al, 2012b;Chakrabarty et al, 2013;Utry et al, 2014), particle soot absorption photometer measurements (Roden et al, 2006), aethalometer measurements (Ganguly et al, 2005), the solar-flux-AOD technique (Russell et al, 2010), integrating plate methods (Schnaiter et al, 2003), differencing extinction and scattering coefficients , or aerosol robotic network (AERONET) retrievals (Bahadur et al, 2012;Chung et al, 2012b;Giles et al, 2012;Cazorla et al, 2013;Xu et al, 2013;Russell et al, 2014).…”
Section: G L Schuster Et Al: Understanding the Aae For Remote Sensmentioning
confidence: 99%
“…For example, Gadhavi and Jayaraman (2010) showed that the spectral dependence of absorbing aerosols can reduce the radiative forcing at top of the atmosphere by about 8%. Over the locations in the central India, Ganguly et al (2005a) found varying nature of composition and sources of absorbing aerosols. Further, they reported up to 30% of excess absorption by absorbing aerosols coming mainly from biofuel burning used for cooking.…”
Section: Introductionmentioning
confidence: 99%